Spatial and Temporal Dynamics of Birch Populations in Residential Areas of St. Petersburg, Russia, from 2002 to 2022 - Kozlov, Mikhail V.; Valdés-Correcher, Elena; Zverev, Vitali (MDPI AG, 2025)
Trees play a vital role in urban landscapes, yet long-term dynamics in tree populations across different levels of urbanization remain poorly understood. We examined whether current spatial patterns of native tree populations predict future changes by monitoring two native birch species (Betula pendula and B. pubescens) in six residential areas of St. Petersburg, Russia. Birch density declined toward the city centre by 1.87 trees ha-1 km-1. From 2002 to 2022, birch populations in sparsely built-up areas (6-8 km from the centre) declined by 0.15 trees ha-1 year-1 due to ageing and urban development, while populations in densely built-up areas near the centre increased by 0.02 trees ha-1 year-1 due to limited tree cutting and greater planting efforts. These trends challenge the assumption that spatial patterns reliably predict temporal changes, emphasizing the complex interplay between ecological and societal factors in urban tree dynamics. We anticipate the continued decline in birch populations in sparsely built-up areas of St. Petersburg over the next 10-20 years until residents recognize the value of their declining greenery and either pressure the city government to intensify planting efforts or begin planting trees themselves.